Pengaruh Kepuasan Nasabah Terhadap Loyalitas Nasabah Pengguna Produk Tabungan Easy Wadiah Pada PT. Bank Syariah Indonesia Tahun 2022 - Febiola, Vani; Iqbal Fasa, Muhammad; Suharto, Prof (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
The development of the banking world in Indonesia is very fast, dynamic and modern, both in terms of the variety of banking products as well as the quality of service and technology owned. Banking is increasingly dominating the economic and business development of a country, not only in developed countries but also in developing countries. The role of banks in the service sector has a very important role in improving service quality and satisfaction for its customers. For this reason, banking management can understand the factors that affect service quality. Islamic banks are financial institutions whose main business is to provide financing and other services in payment traffic and money circulation, whose operations are adjusted to the principles of Islamic law, namely based on the Qur'an and Hadith. , Bank Syariah Indonesia (IDX: BRIS; abbreviated BSI) is a bank in Indonesia that is engaged in Islamic banking. This bank is the result of the merger of Bank Syariah Mandiri, BNI Syariah, and BRIsyariah into one. Bank Syariah Indonesia became a sharia bank owned by HIMBARA (State-Owned Bank Association) with majority (controlling) shares held by Bank Mandiri, so it is considered a subsidiary company in the Mandiri Group.Islamic banks, especially Indonesian Islamic banks, have several superior products, one of which is sharia savings products. In sharia savings, Bank BSI has 2 types of contracts that can be chosen, namely by using wadiah and mudharabah contracts. Wadiah is an activity that includes the safekeeping of goods which is carried out between parties who want to do safekeeping and those who have the power to do safekeeping and gain trust with the aim of maintaining the safety, security, and integrity of the goods or money. Meanwhile, mudharabah is a form of cooperation agreement between the owner of the property and the manager of the property or mudharib. The owner of the property surrenders his property to another party for business. If it is profitable, the profits are divided between the owner of the property and the property manager in accordance with the agreement at the beginning of the agreement. The method used in this problem is descriptive method and associative method.. The results of this study are that there is a positive and quite strong influence between Customer Satisfaction and Customer Loyalty in the Easy Wadiah Savings product of PT. Indonesian Islamic Bank with a correlation value of (+) 0.503. This means that the higher the customer satisfaction, the higher the customer loyalty.